The Effect of Board Independence on the Information Environment and Information Asymmetry - GOH, Beng Wee (Institutional Knowledge at Singapore Management University, 2014)
Our paper examines how the independence of a firm’s board affects its information environment (in terms of earnings quality, management forecast frequency, and analyst coverage) and information asymmetry among investors. We show that greater board independence leads to higher earnings quality, greater management forecast frequency, and broader analyst coverage. We also show that these outcomes mediate the effect of board independence in reducing information asymmetry among investors in the equity markets. Of the three mediators, we find that analyst coverage is the most significant one; this suggests that analysts’ attraction to firms with board independence plays an important role in how board independence affects information asymmetry among investors. Overall, our paper contributes to a better understanding of how board independence influences the trading environment via the information environment.